2022
DOI: 10.1007/s43450-022-00307-0
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Investigation of Egyptian Spinach Leaves, a Potential Source for Antileukemic Metabolites: In Vitro and In Silico Study

Abstract: Spinacia oleracea L., Amaranthaceae, leaves cultivated in Egypt demonstrated a potential antileukemic activity against the chronic myeloid leukemia, K562 cell line. Thus, the aim of this study is to carry out a phytochemical investigation of S. oleracea leaves as well as the isolation of its antileukemic phytoconstituents. Phytochemical investigation of S. oleracea leaves resulted in the isolation of seventeen known compounds. The biological study revealed that compounds hexaprenol, phytol, and 18-[(1-oxohexad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
1
0
0
Order By: Relevance
“…According to the findings of this study, the ethanol extract of S. oleracea (whole plant) contained a high concentration of fatty acids, sterol, diterpenoids, and triterpenes, all of which are known to regulate the antioxidant pathway and modulate inflammatory processes with anti-cancer properties [ 12 , 13 , 14 ]. Similar components were reported by Abdelgawad et al [ 15 ] in their phytochemical analysis of S. oleracea leaves from Egypt. According to the gas chromatography analysis, omega-3 made up the largest proportion of the spinach extract, which is consistent with the findings of Hetta et al [ 16 ], who found that omega-3 is a major component of S. oleracea flowers (30.53%).…”
Section: Discussionsupporting
confidence: 87%
“…According to the findings of this study, the ethanol extract of S. oleracea (whole plant) contained a high concentration of fatty acids, sterol, diterpenoids, and triterpenes, all of which are known to regulate the antioxidant pathway and modulate inflammatory processes with anti-cancer properties [ 12 , 13 , 14 ]. Similar components were reported by Abdelgawad et al [ 15 ] in their phytochemical analysis of S. oleracea leaves from Egypt. According to the gas chromatography analysis, omega-3 made up the largest proportion of the spinach extract, which is consistent with the findings of Hetta et al [ 16 ], who found that omega-3 is a major component of S. oleracea flowers (30.53%).…”
Section: Discussionsupporting
confidence: 87%